TEACHER STRATEGIES IN INCREASING STUDENTS' LEARNING AWARENESS AT MADRASAH - Nuria, Sinta; Mufid, M. Rauhul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research explores teachers' strategies in raising students' learning awareness at MTs Miftahul Ulum Bago Pasirian. Learning awareness is considered key to creating an effective learning environment in this madrasa. Teachers have a vital role in guiding and forming students' learning awareness, which influences motivation, ability improvement, and interpersonal relationships. This research uses a qualitative method with a descriptive approach, collecting data through observation, interviews and documentation. The research results highlight strategies such as providing insight, integrating technology in teaching, evaluating with strategy adjustments, and parental involvement. It is hoped that this research can contribute to the development of science and education in madrasas, especially in the context of increasing students' learning awareness